2016
DOI: 10.1016/j.jcsr.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on demountable shear connectors in composite slabs with profiled decking

Abstract: This paper presents an experimental study on shear strength, stiffness and ductility of demountable shear connectors in metal decking composite slabs through push-off tests.Twelve full-scale push-off tests were carried out using different concrete strength, number of connectors and different connector diameter. The experimental results showed that the demountable shear connectors in metal decking composite slabs have similar shear capacity and behaviour as welded shear studs and fulfilled the minimum ductility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 10 publications
0
26
1
4
Order By: Relevance
“…Experimental studies on demountable shear connectors [39,40] have been carried out. Aninthaneni and Dhakal [41,42] proposed a demountable concrete building system that is suitable for seismic regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experimental studies on demountable shear connectors [39,40] have been carried out. Aninthaneni and Dhakal [41,42] proposed a demountable concrete building system that is suitable for seismic regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A parametric study was then carried out to understand the effect of concrete grades and stud collar sizes on the shear behaviour of the demountable shear connections. Rehman et al [9] conducted twelve full-scale push-off tests on demountable shear connectors in profiled slabs considering different concrete strengths, numbers of connectors per trough and different connector diameters. A reinforcement cage was introduced to prevent pre-mature toe failure of the composite slabs.…”
Section: Universitat Politècnica De Valènciamentioning
confidence: 99%
“…Recent research has shown efforts by the scientific community directed towards understanding the behavior of non-welded connectors, as presented in the works of Rehman et al (2015) [5], Dai et al (2015) [6] and Pathirana et al (2015) [7]. Other recent works have also addressed the study of alternative connectors, developed with the use of materials well known to the construction industry, as may be observed in the research conducted by Barbosa (2016) [8].…”
Section: Introductionmentioning
confidence: 99%